Exploring the effects of COVID-19 on family planning: results from a qualitative study in rural Uganda following COVID-19 lockdown - Katelyn M. Sileo; Christine Muhumuza; Teddy Helal; Allison Olfers; Haruna Lule; Samuel Sekamatte; Trace S. Kershaw; Rhoda K. Wanyenze; Susan M. Kiene (BMC, 2023)
Plain language summary This study explored the potential impact of the COVID-19 pandemic and a 3-month government mandated lockdown on barriers to accessing family planning services in rural Uganda, and recommendations to improve service delivery in the event of future COVID-19 restrictions. Data were collected from four focus group discussions with men and women separately (N = 26) who had an unmet need for family planning, and 15 interviews with community leaders and family planning stakeholders. The delivery of family planning services was disrupted due to COVID-19, negatively affecting community members' ability to access services, such as by reducing their income. COVID-19 also disrupted community and health system distribution of services, such as through a transportation ban and the suspension of all community-based family planning delivery through village health teams and mobile clinics. Participants felt that COVID-19 lockdown restrictions worsened intimate partner violence, and with men at home more, limited women's ability to use contraceptives without their partner's knowledge and resulted in more sex between partners without women being able to refuse. Taken together, these consequences were thought to increase women's risk of unintended pregnancy. Recommendations to improve family planning service delivery in the context of COVID-19 centered on measures to improve the health system's response to emergencies and to safely deliver contraceptive methods directly to communities during future COVID-19 lockdowns. The successful implementation of community-based family planning will depend on efforts to increase men's acceptance of family planning, while addressing underlying gender inequities that diminish women's ability to time and space pregnancy.